Hypermagnesemia Accompanied with Colonic Perforation in a Hemodialysis Patient - Yoon, Hye Eun; Kim, Young Wook; Ha, Kyung Sun; Sim, Eun Hui; Go, Seong Woo; Shin, Seok Joon (Yonsei medical journal, 2013)
We report a case of a chronic hemodialysis patient who developed hypermagnesemia due to an overdose of magnesium-containing laxative and paralytic ileus resulting in colonic perforation. Despite intravenous calcium infusion and daily hemodialysis, the patient developed ischemic colitis and intestinal perforation. Colonic perforation accompanied with hypermagnesemia in hemodialysis patients has rarely been reported. This case suggests that hypermagnesemia should be considered in renal failure patients as this can result in life-threatening events despite prompt treatment.